Understanding the Intention to Use Netflix: An Extended Technology Acceptance Model Approach - Cebeci, Ufuk; Ince, Oguzhan; Turkcan, Hulya (International Review of Management and Marketing, 2019)
Developments in information and communication technologies disrupt the traditional media ecosystem. New media has led to the emergence of many digital platforms such as Netflix. Netflix has become very popular nowadays all over the world. Hence, this paper aims to reveal the determinants of intention to use Netflix based on the technology acceptance model. For this purpose, a survey of 251 respondents in Istanbul was conducted. The findings indicate that (i) self-efficacy and knowledge is positively related to perceived ease of use, (ii) knowledge and perceived ease of use is positively associated with perceived usefulness, (iii) perceived usefulness predicts attitude, (iv) attitude predicts intention to use, and (v) technology anxiety attenuates the positive effect of perceived usefulness on attitude. Keywords: Technology acceptance model, Digital platforms, Netflix JEL Classifications: C42, M31 DOI: https://doi.org/10.32479/irmm.8771